GESTATIONAL TROPHOBLASTIC DISEASE. "INVASIVE MOLE" - Flores C., Luis (2015)
Statistical clinical study of 58 cases of gestational trophoblastic disease that occurred in 30.747 births and 6,506 abortions in the Maternity Hospital of Lima during 1983 was made. Clinically without histopathological confirmation, retrospective diagnosis of invasive mole was made in 14 cases. We show that the incidence of hydatidiform mole and invasive mole is high in our country. The clinical picture of invasive mole is equal to the common mola, however, the symptoms may be more spectacular, which requires additional treatments, as a second curettage, hysterectomy or the use of chemotherapy. There is persistent high rates or chorionic gonadotropin trophoblastic activity and marked with signs of severe atypical of varying degree.